2018
DOI: 10.1002/jsfa.8877
|View full text |Cite
|
Sign up to set email alerts
|

The health‐nutrition dimension: a methodological approach to assess the nutritional sustainability of typical agro‐food products and the Mediterranean diet

Abstract: The proposed sustainability index could be considered a useful tool to describe both the qualitative and quantitative value of micronutrients and bioactive phytochemical present in foodstuffs. This methodological approach can also be applied beyond the Mediterranean, to food products in other world regions. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 197 publications
(307 reference statements)
0
14
0
2
Order By: Relevance
“…It allows the classification of our cheeses, simultaneously taking into account different indicators of human health. Similarly, Azzini et al (2018) identified suitable and easily measurable indicators to assess the nutritional sustainability of several groups of foods. In the current study, the new index was significantly affected by forage species (Figure 1; P < 0.01).…”
Section: Nutritional Indexesmentioning
confidence: 99%
“…It allows the classification of our cheeses, simultaneously taking into account different indicators of human health. Similarly, Azzini et al (2018) identified suitable and easily measurable indicators to assess the nutritional sustainability of several groups of foods. In the current study, the new index was significantly affected by forage species (Figure 1; P < 0.01).…”
Section: Nutritional Indexesmentioning
confidence: 99%
“…4 Many studies have shown that the MD has curative effects on certain blood parameters, especially lipid and glucose profiles, and reduces the risk of metabolic syndrome, type 2 diabetes, cardiovascular diseases (CVD), certain neurodegenerative diseases and cancer. 5–8…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this information must be based on beforehand defined criteria for nutritional sustainability allowing an equivalent measurement system for all companies and stakeholders along the agrifood chain. This is defined as one of the most discussed issue in recent literature about nutritional sustainability—how to measure nutritional sustainability (15, 67). Therefore, one of the main conditions for “nutritional sustainability inside” branding-based communication strategy would be the development of transparent measurement system.…”
Section: Discussionmentioning
confidence: 99%